Methodologies for Socioeconomic Impact Assessment of Agricultural Biotechnology: Lessons from Mexico - Chauvet, Michelle; Solleiro, José Luis; González, Rosa Luz (International Service for National Agricultural Research, 2001)
World trends are now paving the way for increased use of biotechnology. Humankind is facing the challenge to meet the needs of a growing population in the context of reduced food production. In the present context of globalization, agriculture and bioindustries offer new products with increased value added which are well differentiated and capable of meeting the demands and expectations of consumers living mostly in urban areas where the growing integration of women into the work force has changed eating habits, creating more demand for semi-prepared food items. Because of this, food production must now meet stricter quality standards and increased productivity, and conform to more stringent sustainability criteria because of soil fertility loss and global water shortages. Biotechnology has an important role to play in achieving progress in this direction. However, the challenge is even greater as, in addition to quality, productivity and sustainability considerations, new biotechnology products must offer safe alternatives for consumers because of their potential health and environmental effects as they are derived from biotechnology applications on plants and animals.